ANALISIS PENGARUH BRAND IMAGE DAN CORPORATE BRANDING TERHADAP BRAND EQUITY SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN OPERATOR SELULER TELKOMSEL DI KOTA SEMARANG - Purnomo, Singgih; Indriani, Farida (Faculty of Economics and Business Diponegoro University, 2018)
This research aims to find the infulence of brand image and corporate branding on brand equity and its impact on customer loyalty. Furthermore, it aims to find out the role of brand equity in mediating on customer loyalty.This research was conducted on Telkomsel operator customers in Semarang City have been using Telkomsel for minimum one year and had used other celluler operators. Sampling method in this research is non-probability sampling with purposive sampling technique. The number of samples collected as many as 100 respondents through the distribution of questionnaires. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression tests, f-test, determination test, hypothesis test (t statistic test), and Sobel test.The results showed that the variables of brand image and corporate branding in a significantly and positively impact on brand equity. Variable corporate branding has a significant and positive impact on customer loyalty. But the brand image variable has no effect on customer loyalty. Meanwhile brand equity as an intervening variable has a positive and significant impact on customer loyalty.